Swimming speed patterns and stroke variables in the Paralympic 100-m freestyle - Daly, D. J.; Djobova, S. K.; Malone, L. A.; Vanlandewijck, Y.; Steadward, R. D. (Adapted Physical Activity Quarterly, 2003)
A video race analysis was conducted on 100-m freestyle performances of 72 male and 62 female finalists at the Sydney 2000 Paralympic Games. Races were won or lost in the second half of each 50-m race lap and differences in speed between swimmers were more related to stroke length than stroke rate. Within-race speed changes were more related to changes in stroke rate. Stroke rate changes were also responsible for speed changes between qualifying heats and finals in the first part of races, while stroke length was responsible for better speed maintenance at the end of races. Results indicate that Paralympic finalists use race speed patterns similar to able-bodied elite swimmers.